Wireless Rogowski coil sensor based on partial discharge detection signal for on-line condition monitoring in the medium voltage power cables - Mohamad Nur Khairul Hafizi, Rohani (Universiti Malaysia Perlis (UniMAP), 2017)
Doctor of Philosophy in Electrical Systems Engineering